Pararretal Hematoma after Delivery - Oliveira, M (2019)
A puerperal vulvovaginal hematoma is not an unusual finding after vaginal deliveries. However, most of them are small and self-limited. Even though there are multiple risk factors identified, the majority of cases happen in low risk settings. We here report a case of a nulliparous young woman who developed a massive pararretal hematoma after an uncomplicated vaginal delivery. Surgical intervention was useful but selective embolization was required. Our goal is to highlight the importance of being aware of this potential complication of a vaginal delivery and the need of an early diagnosis in order to offer the most suitable treatment and prevent severe damages.